Transforming Religious and Monarchial Power: The Iron Gate of Ganja within the Gelati Monastery - Hubbert, Jake (Journal of Islamic Archaeology, 2023)
The political landscape of the emergent medieval Georgian nation among the predominant Islamic emirates is a relatively new field for western scholars. The Medieval Georgian polity, led by King Davit IV (Aghmshenebeli), rose to power in the late 11th and early 12th centuries CE. As the crowning jewel of a new architectural scheme, King Davit IV constructed the Gelati Monastery as a symbol of political, social, and religious power in medieval Georgia. King Davit IV’s son, King Demet’re I, finished the monastery in the 12th century and added to its construction with one fundamental piece, the iron gates of Ganja. The gates, taken by King Demetrius I from the Islamic city of Ganja in 1139 CE as a spoil of war, were placed next to the grave of King Davit IV Aghmshenebeli. My paper investigates the symbolic importance of the gates from Ganja in its original context for the local Ganjans and what it later meant to the Georgians. I also address the types of peoples involved with the transformation of the gate’s power as it moved locations. These gates have an Arabic inscription on them that indicates the original purpose of the gates for the Islamic ruler of Ganja. A translation of the Arabic script on the gates is also given in my paper. Finally, I demonstrate how the meanings of the gates of Ganja changed as King Demet’re I moved them from Ganja to their final destination within the Gelati complex and how those meanings related to the political landscape that the Medieval Georgian Kingdom sought to create.